The impact of bariatric surgery on female reproductive health - E. Kh. Chigisheva; I. I. Batyrshin; A. F. Sarvalieva; I. V. Khalitova; T. M. Zhuk; L. V. Evdokimova; M. A. Akbulatova; Ya. R. Zolotareva; L. M. Zainysheva; S. Baloyan; E. M. Dragunova; A. A. Korenkova; et al. (Акушерство, гинекология и репродукция, 2024)
Introduction. Obesity is a worldwide problem at epidemic scale. Bariatric surgery (BS) is the most effective method to treat morbid obesity characterized by long-term and positive effects on concomitant diseases. However, the effect of BS on female reproductive health has not been sufficiently studied to date, which makes relevant to conduct further investigations in this field.   Aim: to summarize research data assessing BS effect on female reproductive health.   Materials and Methods. There was conducted a search for publications in the electronic databases PubMed, eLibrary and Google Scholar to identify the following keywords and their combinations in Russian and English: "bariatric surgery", "reproductive health", "sex hormones", "pregnancy", "menstrual cycle", "fetal", "neonatal". The evaluation of the articles was carried out in accordance with the PRISMA recommendations. Based on search data, 868 publications from PubMed, 83 publications from eLibrary and 74 publications from Google Scholar were retrieved. After the selection procedure, 79 articles were included in the review.   Results. To date, the data regarding the long-term BS effects on improved obesity-related endocrine disorders remain insufficient. It is better to recommend long-acting reversible contraceptives such as intrauterine device, to post-BS patients. Women with BS history should have a continuous comprehensive nutritional assessment as well as blood macronutrients and trace elements monitoring before, during and after pregnancy. Recognizing potential complications associated with BS in the anamnesis and timely seeking specialized medical aid or timely transfer of a patient to a specialized medical facility may improve pregnancy outcomes for a mother and paired newborn.   Conclusion. While making decision to perform BS, it is necessary to fully understand its impact on female reproductive health, assess patients' reproductive intentions and fulfill health education obligations. All patients of childbearing age who are candidates for BS should participate in a joint decision-making dialogue on BS-related risks and benefits for reproductive health, which should be supported by extensive multidisciplinary work involving obstetricians, gynecologists, endocrinologists, psychologists and representatives of other medical specialties. To date, the data regarding the BS-related effects on pregnant women are heterogeneous, which requires additional investigations in this field.